Mapping the risky returns to smallholder fertilizer investments in Africa - Gebrekidan, Bisrat; Chamberlin, Jordan; Mkondwa, Maxwell; Silva, Joao Vasco; Hijmans, Robert (International Maize and Wheat Improvement Center, 2025)
Low and inconsistent use of inorganic fertilizer continues to constrain agricultural productivity growth in sub-Saharan Africa, despite strong agronomic evidence of yield responsiveness in maize-based systems. A central challenge is that fertilizer decisions are made under substantial production and market uncertainty, yet most policy targeting and advisory tools rely on average profitability metrics that mask exposure to downside risk. This paper develops a spatially explicit, ex ante framework to support risk-informed fertilizer policy and investment decisions under rainfed smallholder conditions. We integrate georeferenced maize fertilizer trial responses with spatial data on soils, long-run rainfall variability, remotely sensed vegetation, and locally differentiated input and output prices to characterize the full distributions of fertilizer returns across space. Production risk, price volatility, and crop failure are modeled explicitly, including their joint dependence through spatial rainfall and price relationships. The results show that areas with high expected returns frequently face a substantial probability of financial loss, driven by the interaction of climatic variability, market volatility, and catastrophic production risk. Accounting for these risks identifies spatial “risk traps” where fertilizer is technically productive but economically unattractive for risk-averse farmers. The framework provides guidance for the spatial targeting of fertilizer subsidies, extension, insurance, and complementary market interventions, helping policymakers and investors prioritize locations where fertilizer use can be both profitable and resilient, and tailor risk-mitigation instruments where uncertainty remains binding.